How host–guest interaction types shape value co-creation in urban tourism: The moderating role of AI technology stimuli - Guanxi Chen; JiaJun Chen (PLoS ONE, 2026)
This study examines how different types of host–guest interaction relate to tourists’ value co-creation intention in urban tourism and whether artificial intelligence technology stimuli moderate these relationships. Grounded theory was used to identify the main constructs and relationships. Survey data were then analyzed using partial least squares structural equation modeling, and fuzzy-set qualitative comparative analysis was conducted to identify configurations associated with high value co-creation intention. The results showed that tourist–government interaction and tourist–resident interaction were positively related to tourist empowerment, and tourist empowerment was positively related to value co-creation intention. Neither tourist–government interaction nor tourist–resident interaction had a direct relationship with value co-creation intention. Artificial intelligence technology stimuli moderated the paths from tourist–government interaction to tourist empowerment and from tourist–government interaction to value co-creation intention. No moderating effect was found for the tourist–resident interaction paths. The fuzzy-set qualitative comparative analysis identified multiple configurations associated with high value co-creation intention.